Rectovesical Fistula Related to Transurethral Resection of a Bladder Lesion - Ramazan Topaktaş; Abdulkadir Tepeler; Omer Kurt; Mehmet Remzi Erdem; Abdullah Armağan; Şinasi Yavuz Önol (Case Reports in Medicine)
A rectovesical fistula (RVF) is an uncommon complication of urooncologic surgery. Although several RVFs have been reported, our case is the first reported RVF in the literature that iatrogenically occurred after transurethral resection of the bladder. A single-stage primary repair with omental flap interposition without a colostomy was successfully performed because of the persistence of the fistula during followup. After 6 months of followup, no fistula or bladder mass was detected.